Policies for Addressing Cybersecurity Challenges in the European Union - Mahmood, Asst. Prof. Dr. Senaa Ali (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2026)
This study examines the European Union’s policies for addressing cybersecurity challenges through an analysis of the institutional framework underpinning these policies and an assessment of the effectiveness of public policy in responding to the growing spectrum of cyber threats. As cybersecurity has emerged as a fundamental pillar of political, economic, and digital stability, the European Union has progressively developed an integrated framework of institutions, legislation, and regulatory mechanisms aimed at strengthening digital security, enhancing coordination among EU institutions and Member States, and improving their capacities to prevent, mitigate, and respond to cyber risks. The study further explores the nature of cybersecurity challenges and their influence on European public policymaking, with particular emphasis on the role of the European Union Agency for Cybersecurity (ENISA) in advancing digital governance, fostering institutional cooperation, facilitating information sharing, and strengthening institutional capabilities. It also reviews the most significant legislative developments in this field, particularly the Directive on Measures for a High Common Level of Cybersecurity across the Union (NIS2 Directive) and the Cyber Resilience Act. The findings indicate that the European Union has succeeded in establishing a relatively advanced institutional and legislative framework for cybersecurity. Nevertheless, achieving higher levels of policy effectiveness requires deeper institutional integration, reducing disparities among Member States, and further enhancing coordination and response mechanisms to keep pace with the rapidly evolving cyber threat landscape.